At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To convert the function [tex]\( f(x) = 4(x + 6)^2 + 5 \)[/tex] into its standard form [tex]\( f(x) = ax^2 + bx + c \)[/tex], let's follow the steps of expanding and simplifying the given expression.
1. Expand the binomial:
[tex]\[ (x + 6)^2 = x^2 + 12x + 36 \][/tex]
2. Multiply the binomial term by 4:
[tex]\[ 4(x^2 + 12x + 36) = 4x^2 + 48x + 144 \][/tex]
3. Add the constant 5:
[tex]\[ 4x^2 + 48x + 144 + 5 = 4x^2 + 48x + 149 \][/tex]
The standard form of the function is:
[tex]\[ f(x) = 4x^2 + 48x + 149 \][/tex]
Thus, the coefficients are:
[tex]\[ a = 4, \quad b = 48, \quad c = 149 \][/tex]
1. Expand the binomial:
[tex]\[ (x + 6)^2 = x^2 + 12x + 36 \][/tex]
2. Multiply the binomial term by 4:
[tex]\[ 4(x^2 + 12x + 36) = 4x^2 + 48x + 144 \][/tex]
3. Add the constant 5:
[tex]\[ 4x^2 + 48x + 144 + 5 = 4x^2 + 48x + 149 \][/tex]
The standard form of the function is:
[tex]\[ f(x) = 4x^2 + 48x + 149 \][/tex]
Thus, the coefficients are:
[tex]\[ a = 4, \quad b = 48, \quad c = 149 \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.